The height Digital Image Correlation (hDIC) technique for the identification of triaxial surface deformations. (August 2019) - Uzun, Fatih; Korsunsky, Alexander M.
Highlights: The height digital image correlation (hDIC) technique for the identification of triaxial deformations is introduced. Out-of-plane surface height and its variation during deformation are used for the correlation process. Triaxial Cartesian coordinate data of reference and target data sets are cross-correlated at integer-pixel level sensitivity. Sub-pixel registration is performed using gradient descent method. Abstract: This paper introduces the height digital image correlation (hDIC) technique for the identification of triaxial deformations. Conventional digital image correlation (DIC) uses pixel image intensity as the basis for the determination of in-plane displacement fields. We demonstrate the advantages of using the out-of-plane surface height and its variation during deformation to extract information about triaxial (in-plane and out-of-plane) displacement fields. Surface height maps can be obtained by optical profilometry or scanning probe microscopies, e.g. stylus profilometry, coordinate measurement machine (CMM), or atomic force microscope (AFM). The changes in height during deformation are sufficiently small to allow efficient correlation of in-plane displacements with sub-pixel accuracy, yet also provide information about out-of-plane displacements. In the present study, the contour map of surface height was created using digital dynamic focus ("deep focus") optical microscope. The correlation between the reference and target maps to extract the displacement data was accomplished by a two-step correlation process. Initially, triaxial Cartesian coordinate data of reference and target data sets were cross-correlated at integer-pixel level sensitivity. This was followed by sub-pixel correlation using gradient descent method. As an example of technique application, Al alloy test specimens were subjected to large tensile deformations to failure. Good agreement was found between height digital image correlation (hDIC) analysis of displacements and strains and the reference material properties, with the evolution of both in-plane strains and out-of-plane displacements showing progressive localisation during post-critical deformation beyond the sample's ultimate tensile strength (UTS). Graphical abstract: Image, graphical abstract